Comparison of AHP and SAW Methods for Predicting Career Interests of SMAN 1 Karanganyar Demak Students - Prabowo, Ardian Adi; Supriyanto, Aji (Sistemasi: Jurnal Sistem Informasi, 2025)
This study compares the efficacy of the Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods in predicting career interests of students at SMAN 1 Karanganyar Demak. The research assesses seven key factors: familial influence, educational engagement, individual capabilities, academic performance, institutional resources, resilience of a career, and academic interests. Results show that AHP prioritizes familial influence (28.94%), individual capabilities (17.10%), and educational engagement (16.23%), while SAW highlights career (15.75%), educational engagement (15.61%), and individual capabilities (14.92%). Both methods achieved an accuracy of 83.02%. Career recommendations were categorized into guidance-intensive cases (AHP: 42.68%; SAW: 46.00%), employment-oriented individuals (AHP: 33.96%; SAW: 32.97%), higher education aspirants (AHP: 12.94%; SAW: 10.06%), and entrepreneurial prospects (AHP: 10.42%; SAW: 10.96%).